Membangun Ekonomi Berbasis Akhlaq dan Syariah: Tantangan dan Peluang - Arwani, Arwani; Oktaviani, Nuni; DwiKurniadi, Septian (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2024)
Building an Economy Based on Akhlaq and Shariah presents significant challenges and opportunities in the context of current economic globalization. This paper explains the importance of integrating akhlaq and shariah principles in developing a sustainable and just economy. This research uses both qualitative and quantitative approaches to investigate the challenges and opportunities in building an economy based on akhlaq and shariah. The findings indicate that an economy model based on akhlaq and shariah offers a significant alternative to conventional models with principles of distributive justice, environmental sustainability, and financial inclusion that are relevant for building a more just and inclusive society. However, its implementation faces challenges such as a lack of understanding, resistance to change, legal uncertainty, and infrastructure deficiencies. Institutional and regulatory transformation, including the development of shariah-compliant financial institutions and policy reforms, is crucial for creating a supportive environment. Technology, such as fintech and blockchain, can enhance access and efficiency of shariah-compliant financial services. Collaboration across disciplines and stakeholders is needed to develop a holistic and sustainable framework. Keywords: Economy, Akhlaq, Sharia, Challenges, Opportunities